Banking with Agents : Experimental Evidence from Senegal - Buri, Sinja; Cull, Robert; Gine, Xavier; Harten, Sven; Heitmann, Soren (World Bank, Washington, DC, 2018)
This paper uses a randomized controlled trial to study the effects of access to agent banking. Individuals were encouraged to open an account and transact at a banking agent or a branch of a financial institution. Compared with individuals who were sent to the branch, individuals sent to an agent increased the number of transactions and incurred lower transaction costs with the agent. These transactions are, however, only half as large as those made at the branch because branch tellers are less likely to share information about clients with others. Banking with agents thus entails a trade-off between lower transaction costs and lack of privacy.